Review of Self+Culture+Writing: Autoethnography for/as Writing Studies, Rebecca Jackson and Jackie Grutsch McKinney, editors - Amanda E. Scott (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
This volume brings together a compendium of works that explore autoethnography and its emerging applications. A qualitative approach that first appeared in the social sciences, autoethnography has recently gained traction within other disciplines over the last two decades, including rhetoric and composition studies. However, due to its theoretically and methodologically amorphous qualities, over the years researchers have struggled to firmly define autoethnography, especially as the field continues to evolve. Still, many within writing studies have championed the method and now understand it as a recursive tool for studying “the relationship between self and other and all of its dimensions” (Kafar and Ellis 134).
Keywords: JAEPL